2021
DOI: 10.1590/1984-3143-ar2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

Use of pyridoxine hydrochloride in the interruption of lactation in female dogs with pseudopregnancy

Abstract: The aim of this research was to evaluate the use of pyridoxine hydrochloride and its associated side effects in the treatment of pseudopregnancy in female dogs. A total of 40 female dogs, with no defined breed, in non-gestational diestrus, with clinical complaint of milk production were selected. The female dogs were divided into four experimental groups of 10 animals each, treated orally for 20 days with 10mg/kg/day (G1) and 50mg/kg/day (G2) of pyridoxine hydrochloride (vitamin B6), 5μg/kg/day of cabergoline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A study in dogs also found that PN at different intake levels (10 mg/kg bw per day and 50 mg/kg bw per day for 20 days) could suppress lactation at the highest dose (da Silva et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 95%
“…A study in dogs also found that PN at different intake levels (10 mg/kg bw per day and 50 mg/kg bw per day for 20 days) could suppress lactation at the highest dose (da Silva et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 95%
“…could suppress lactation in a dose-dependent manner, with no side effects reported (da Silva et al, 2021).…”
Section: Anti-lactogenic Effectmentioning
confidence: 88%
“…Such a syndrome is due to the physiological drop in blood P4 levels by the end of the dioestrus phase, which is also associated, in some female dogs, with a release of prolactin. Galactorrhoea is, therefore, a consequence of the physiological hormonal pattern of the sexual maturity in dogs and should not be considered as a side effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%